Immigration and Integration in Israel and Beyond - Hochman, Oshrat (Kultur und soziale Praxis., 2023)
Immigration is a persistent and complex phenomenon intertwined with geographical, political, societal, and economic challenges. The number of international migrants has been continually increasing over the past five decades. The contributors to this volume dedicated to Professor Rebeca Raijman address various types of migrants like economic or labour migrants, forced migration and ethnic migrants. Implementing both qualitative and quantitative data and analyses, they provide insight on why individuals decide to migrate, how their decisions affect their own lives and the lives of their offspring, and how immigrants affect the receiving societies they arrive in.